Evaluation of maximum power point tracking in hydrokinetic energy conversion systems. Issue 11 (23rd November 2015) - Khan, Jahangir; Iqbal, Tariq; Quaicoe, John
Abstract : Maximum power point tracking is a mature control issue for wind, solar and other systems. On the other hand, being a relatively new technology, detailed discussion on power tracking of hydrokinetic energy conversion systems are generally not available. Prior to developing sophisticated control schemes for use in hydrokinetic systems, existing know‐how in wind or solar technologies can be explored. In this study, a comparative evaluation of three generic classes of maximum power point scheme is carried out. These schemes are (a) tip speed ratio control, (b) power signal feedback control, and (c) hill climbing search control. In addition, a novel concept for maximum power point tracking: namely, extremum seeking control is introduced. Detailed and validated system models are used in a simulation environment. Potential advantages and drawbacks of each of these schemes are summarised.